Non-linear maker pedagogy in Finnish craft education - Härkki Tellervo; Seitamaa-Hakkarainen Pirita; Vartiainen Henriikka; Saarinen Auli; Hakkarainen Kai (Oslo and Akershus University College, Learning Centre and Library, 2025)
This research explores the use of a non-linear maker pedagogy for implementing a major change in the Finnish national core curriculum. The latest curriculum change (2014) introduced so-called transversal competences, but also a major change for the subject of crafts: ‘multi-material’ crafts that involve former separately taught textile and technical crafts both now introduced to all pupils. These changes set the stage for in-service teacher training, as well as for pedagogical solutions, such as a non-linear maker pedagogy and closer collaboration between technical and textile craft teachers. A non-linear maker pedagogy refers to an approach combining several features: a shift from individual learning and solo teaching to collaborative knowledge-creating learning, opportunities for collective invention and improvisation, pupil-centred situated inquiry and the creation of artefacts that combine material and digital realms. In this collective case study, we interviewed six teachers who co-taught non-linear maker projects in six different schools. Through a qualitative content analysis, we identified successes and challenges regarding the use of a non-linear maker pedagogy, pupil collaboration and teaching digital skills through robotics and e-textiles. In the interviews, teachers reflected on their work mainly by describing their pupils’ accomplishments, reactions and learning. These reflections indicated similar challenges and successes, suggesting that the variation between pupils and pupil groups was larger than that between schools. Furthermore, we discuss whether the selected pedagogical approach was unduly ambitious. Despite all the challenges, most of the teachers expressed their commitment to developing their teaching practices along the lines of a non-linear maker pedagogy.